ANALISA USAHA PETERNAKAN AYAM PETELUR SISTEM CLOSED HOUSE DI ROSSA FARM DESA KENDALREJO KECAMATAN SRENGAT KABUPATEN BLITAR - Rany Dwi Ramadhani (AVES: Jurnal Ilmu Peternakan, 2017)
This research was conducted at laying hens Rossa Farm,Blitar regency. The objective of the research is to know how big the profit and feasibility level at laying hens Rossa Farm by using cage with closed house system in terms of economic analysis. Based on the calculation of profits in economic analysis of laying hens Rossa Farm value of R/C ratio 2017 is 1.11. While the BEP results and prices for the year 2017 is 2,015,022.1 kg and Rp. 15.425,89,-. The margin of safety value of whole egg sales in 2017 that is 10,41%. While the result of business feasibility calculation NVP value obtained from the farming business of laying hens Rossa Farm is Rp. 2.14.131.163,9,- and the IRR value obtained is 20,13% or more than the 12% discount rate, then this business is feasible to run. Keywords : Closed house system, economic analysis.